2023
DOI: 10.1111/gcb.17024
|View full text |Cite
|
Sign up to set email alerts
|

Formation of mineral‐associated organic matter in temperate soils is primarily controlled by mineral type and modified by land use and management intensity

De Shorn E. Bramble,
Susanne Ulrich,
Ingo Schöning
et al.

Abstract: Formation of mineral‐associated organic matter (MAOM) supports the accumulation and stabilization of carbon (C) in soil, and thus, is a key factor in the global C cycle. Little is known about the interplay of mineral type, land use and management intensity in MAOM formation, especially on subdecadal time scales. We exposed mineral containers with goethite or illite, the most abundant iron oxide and phyllosilicate clay in temperate soils, for 5 years in topsoils of 150 forest and 150 grassland sites in three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 130 publications
(210 reference statements)
0
4
0
Order By: Relevance
“…These findings confirm the low pedogenetic development of the parent material (i.e., loess-deposits) . These properties did not support an extensive surface area for physicochemical protection (i.e., organo-mineral association, coprecipitation, and occlusion inside stable soil aggregates of organic matter) from degradation which is better provided by Al- and Fe-oxyhydroxides than by phyllosilicates. , Such mechanisms are the primary drivers for C stabilization in developed soils. …”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…These findings confirm the low pedogenetic development of the parent material (i.e., loess-deposits) . These properties did not support an extensive surface area for physicochemical protection (i.e., organo-mineral association, coprecipitation, and occlusion inside stable soil aggregates of organic matter) from degradation which is better provided by Al- and Fe-oxyhydroxides than by phyllosilicates. , Such mechanisms are the primary drivers for C stabilization in developed soils. …”
Section: Resultsmentioning
confidence: 78%
“…17 These properties did not support an extensive surface area for physicochemical protection (i.e., organo-mineral association, coprecipitation, and occlusion inside stable soil aggregates of organic matter) from degradation which is better provided by Al-and Feoxyhydroxides than by phyllosilicates. 36,78 Such mechanisms are the primary drivers for C stabilization in developed soils. 79−88 Sowers et al, 22 using microfocused synchrotron-based XRF, showed a correlation between Fe and C in the sample investigated in this research, suggesting colocalization and potential interaction.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the soil becomes more susceptible to various forms of degradation, including acidification, wind and water erosion, low water retention, and pedocompaction. Bramble et al (2024), Karabcová et al (2015), and Pospíšilová et al (2011) discussed the opposite effect of fertiliser on SOM, where fertiliser positively increases plant production but reduces species diversity in grassland. Simiraly to us, they demonstrated that SOM accumulation in temperate grasslands is affected by management practices and fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Organic C in the soil is derived mainly from plant and animal residues, which enter the soil and pass through soil microorganisms before transformation into SOC . Soil microorganisms have a dual role in controlling SOC: catabolic, as they decompose organic compounds, and anabolic, as they stabilize C formation and thus more stable SOC. , The size of SOC has undergone dynamic changes driven by climatic (temperature and moisture) and soil (pH, texture, and minerals) conditions, soil fauna, and complex plant–soil–microbial interactions . Especially in forested ecosystems, plant symbionts and mycorrhizal fungi (MF), fueled by plant C allocation of recent photosynthates, may significantly contribute to the soil organic matter (SOM) decomposition and mining for N from soil .…”
Section: Soc Formation Stabilization and Decompositionmentioning
confidence: 99%